Statistical analysis of some mechanical properties of friction stir welded aluminium matrix composite. (1st January 2012) - Hassan, Adel Mahmood; Almomani, Mohammed; Qasim, Tarek; Ghaithan, Ahmed
In this study, the effect of friction stir welding (FSW) parameters such as rotational speed, welding (transverse) speed, and the type of pin profile tool on some mechanical properties was statistically investigated. Plates of aluminium matrix composites fabricated by stir casting method were joined by friction stir welding process. The statistical analysis has shown that the most important factor affecting hardness and tensile strength is the welding (transverse) speed, while the rotational speed has a second ranking and pin profile tool geometry is the least. The rotational speed has no statistical significant influence on the wear rate. However, the nugget zone, which was welded by square pin profile tool, seemed to exhibit better mechanical properties compared to those obtained by other pin profile tools.